Apelatywizacja nazw własnych z obszaru literatury (na materiale z języka ogólnego i slangu młodzieżowego) = Appellativization of proper names of literary origins (based on contemporary Polish language and students` slang) - Łukowiak, Dominik (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The focal issue of this paper is one of the ways of forming new language units - the notion of appellativization of proper names that occur in contemporary Polish language as well as in school and university students` slang. The considerations are devoted to eponyms, that is words which have undergone the process of appellativization, derived from the thematic area of literature, especially from names of literary characters.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie